BAHASA DAN IDENTITAS: Dinamika Kebudayaan Lampung di Tatar Sunda - Zahwa, Alvina Maza; Sandi, Ahmad; Hikmah, Tamara Siti; Badriah, Lelis Lailatul; Hamid, Abd Rahman; Setiawan, Agus Mahfudin (Universitas Banda Naira, 2025)
This study examines the history, existence, and preservation of the cultural identity of the Lampung people in Cikoneng Village, Banten, as a Lampung village in Sundanese Tatar. The arrival of the Lampung people to Banten was influenced by the pepper trade, the spread of Islam, and the involvement of the Lampung military in the expansion of the Banten region. In its development, Lampung culture in Cikoneng has shifted due to acculturation with Sundanese and Javanese culture of Banten. The village burning incident by DI/TII in 1958 also destroyed Lampung's traditional houses, leaving the Lampung language as the main cultural identity that still survives. Other cultural symbols that still exist are the Darul Falah Mosque and the Tomb of Minak Sengaji. This study uses historical methods by combining written sources and oral traditions through interviews. The results of the analysis show that the preservation of Lampung's culture faces challenges due to cultural openness and a lack of collective efforts. Despite the mixing of dialects and adaptations of other cultures, the Cikoneng people still maintain the Lampung language is a form of their pride and ethnic identity.